The assessment of pharmacoeconomic studies quality of Levodopa’s use for the management of Parkinson’s diseases, 2010-2015 (2017)
Levodopa (LD) has been the first choice in the management of Parkinson’s disease(PD), since its introduction in the drug market; however, its prolonged use is related tothe occurrence of motor complications, affecting the functionality and quality of life.Parkinson’s disease is one of the most frequent among the neurodegenerative diseasesin the world, and it is expected that the number of people who suffer it, will increasedue to global population aging. The PD represents, nowadays and for the future, ahigh economic burden from all perspectives, including patients, payers, and society.So it is necessary to know about the use of LD in its treatment and to realize thequality of pharmacoeconomic studies in the past five years, to identify reliable sourcesof information related to the costs and benefits of this medication to contribute inmaking decisions. The aim of this paper is to assess the methodological quality ofpharmacoeconomic studies related to the use of LD in PD, specifically those that areidentified as cost-utility studies, applying the QHES instrument. A total of 19 articleswere found, of which 5 met the inclusion criteria and were subjected to examination.The average overall score obtained after the evaluation was 77.2 out of 100, makingevident a good quality of studies according to the method used.